Forecasting the probability of commercial wind power development in lagging countries - Zwarteveen, Jan Willem; Angus, Andrew (Elsevier, 2022)
There is significant under-utilization of wind energy resources, particularly in countries that have high wind potential. From the 67 highest wind potential countries, 39 have installed less than 500 ​MW of wind power capacity, while the remaining countries have an average installed capacity of 20,596 ​MW. In the lagging countries, there is significant potential for sustainable value creation, however large investment gaps need to be closed. Entering a new market for wind power Original Equipment Manufacturers is complex and requires a prediction of the future market size. Quantitative research to promote wind power internationalization is scarce. The objective of this paper is therefore to estimate the market size by predicting the probability of commercial wind development in the lagging countries. The purpose is to help the Original Equipment Manufacturers in their market entry decisions. The second purpose is to provide an example how to reduce risk required to close the Sustainable Development Goals financing gap. Using a binary logistic regression model based on technological path creation theory, the probability for the 39 lagging countries to enter the wind power commercialization stage was predicted. Results show that 12 of the lagging countries have a high probability to commercialize wind energy. A new simulation-based approach was presented to stimulate wind power market entry. The prediction of adoption probability proves useful to reduce risk required to close the financing gap to achieve the Sustainable Development Goals.
Keywords: Market entry strategy; Original equipment manufacturer; SDG; Financing gap; Wind energy